Utilizing Osteocyte Derived Factors to Enhance Cell Viability and Osteogenic Matrix Deposition within IPN Hydrogels. - Hoey, David (My University, 2020)
Many bone defects arising due to traumatic injury, disease, or surgery are unable to regenerate, requiring intervention. More than four million graft procedures are performed each year to treat these defects making bone the second most commonly transplanted tissue worldwide. However, these types of graft suffer from a limited supply, a second surgical site, donor site morbidity, and pain. Due to the unmet clinical need for new materials to promote skeletal repair, this study aimed to produce novel biomimetic materials to enhance stem/stromal cell osteogenesis and bone repair by recapitulating aspects of the biophysical and biochemical cues found within the bone microenvironment. Utilizing a collagen type I–alginate interpenetrating polymer network we fabricated a material which mirrors the mechanical and structural properties of unmineralized bone, consisting of a porous fibrous matrix with a young’s modulus of 64 kPa, both of which have been shown to enhance mesenchymal stromal/stem cell (MSC) osteogenesis. Moreover, by combining this material with biochemical paracrine factors released by statically cultured and mechanically stimulated osteocytes, we further mirrored the biochemical environment of the bone niche, enhancing stromal/stem cell viability, differentiation, and matrix deposition. Therefore, this biomimetic material represents a novel approach to promote skeletal repair.
PUBLISHED
Keywords: Bone; Collagen type I; Alginate; Conditioned medium; Viability; MSC; Osteogenesis